2012
DOI: 10.1002/adsc.201200412
|View full text |Cite
|
Sign up to set email alerts
|

Dual Heterogeneous Catalysis for a Regioselective Three‐ Component Synthesis of Bi‐ and Tri(hetero)arylpyridines

Abstract: International audienceWe designed a new, user-friendly oxidative dual heterogeneous catalytic system capable of promoting polysubstituted pyridines as unique products from simple activated Michael acceptors, 1,3-dicarbonyls and ammonium acetate. This metal-free environmentally-respectful and totally regioselective domino reaction proved to be a great strategy to access bi- and tri-aryl type pyridines as well as challenging bi- and tri-heteroaryl type pyridines in a single operation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 113 publications
1
12
0
Order By: Relevance
“…It has undergone many modifications and improvements and is now the method of choice for fast access to DHP derivatives, which are useful for various bioactivities such as calcium channel blockers and antihypertensive agents [ 10 , 46 ] but, also, as scaffolds in medicinal chemistry [ 14 ]. Under oxidative conditions, these so-called Hantzsch esters can be transformed into the corresponding pyridines, a strategy used to prepare single regio-isomers of poly-substituted pyridines [ 47 , 48 , 49 ] ( Scheme 9 ).…”
Section: The Hantzsch Reactionmentioning
confidence: 99%
“…It has undergone many modifications and improvements and is now the method of choice for fast access to DHP derivatives, which are useful for various bioactivities such as calcium channel blockers and antihypertensive agents [ 10 , 46 ] but, also, as scaffolds in medicinal chemistry [ 14 ]. Under oxidative conditions, these so-called Hantzsch esters can be transformed into the corresponding pyridines, a strategy used to prepare single regio-isomers of poly-substituted pyridines [ 47 , 48 , 49 ] ( Scheme 9 ).…”
Section: The Hantzsch Reactionmentioning
confidence: 99%
“…In some instances, the use of stoichiometric amounts of MnO 2 replacing acetic acid and activated carbon was found to be essential. 42 The use of 1,3-dicarbonyl derivatives such as 51 limited the synthesis to pyridines with a 3-carbonyl substituent. However, in 2015, Chunyin Zhu reported that aldehydes and ketones 59 could also take part in this multicomponent reaction in the presence of an amine 60 and a catalytic amount of CAN.…”
Section: Scheme 16 Synthesis Of 2346-tetrasubtituted Pyridines 58 mentioning
confidence: 99%
“…As an improvement of this methodology, the use of activated Michael acceptors 2 (R 5 = EWG) under appropriate heterogeneous oxidative conditions combining molecular sieves with activated carbon allowed the introduction of various functionalities at the strategic C‐212 and C‐413 positions of the heteroaryl ring (Scheme , method B denoted “dual heterogeneous catalysis”) 14. This environmentally friendly methodology has proved to be a valuable strategy for the challenging metal‐free access to di‐ and tri(hetero)arylpyridines 15…”
Section: Introductionmentioning
confidence: 99%